The Utilization of Social Media and the Reinforcement of National Identity in Generation Z - Exti Budihastuti; Anggi Auliyani Suharja; Emma Maemunah; Sang Ayu Putu Eny Parwati; Ade Mulyanah; Sariah; Rini Widiastuti; Ery Agus Kusnanto; Kaniah (BRIN Publishing (Penerbit BRIN), 2024)
Generation Z is the generation born after the Millennial Generation. The birth year gap of Generation Z is considered the generation that was born farthest from the history of the birth of the Indonesia nation. There are still many people who doubt the power of national identity in Generation Z who was born at a time when technology is experiencing rapid advancement. The rapid progress in the field of communication has made children born in Generation Z more quickly acquainted with social media, both in the fields of Education, General Knowledge, Entertainment, and Lifestyle. Therefore, research was conducted to find out the use of social media and strengthening national identity in Generation Z to dismiss public doubts about strengthening national identity. This study aims to find out the use of social media and the strengthening of national identity in Generation Z. Social media in question is Instagram which is used among teenagers aged 18 to 22 years. The research method used is a qualitative quantitative method. The respondents of this study were 42 students of state universities in Jakarta. The data was processed using the Miles and Huberman method. The data processing technique uses Miles and Huberman. The results of this study are also expected to be a recommendation to determine the policy of using social media among Generation Z and strengthening national identity.